Recognizing and limiting syphilis to prevent congenital syphilis. Issue 8 (August 2020) - Sanchez, Lucia; Harris, Toni; Duford, Amie; Duran, Nelson
Abstract : ABSTRACT: Syphilis is on the rise in every age and ethnicity group across the United States. The rate of congenital syphilis has started to rise as well, increasing the need for syphilis screening before pregnancy occurs. Raising awareness for syphilis screening, especially among sexually active women, is important, as the implications of this disease have lifelong effects for mother and child.